Enhancing long‐term storage and stability of engineered living materials through desiccant storage and trehalose treatment. Issue 2 (1st November 2022) - Brooks, Sierra M.; Reed, Kevin B.; Yuan, Shuo‐Fu; Altin‐Yavuzarslan, Gokce; Shafranek, Ryan; Nelson, Alshakim; Alper, Hal S.
Abstract: Engineered living materials (ELMs) have broad applications for enabling on‐demand bioproduction of compounds ranging from small molecules to large proteins. However, most formulations and reports lack the capacity for storage beyond a few months. In this study, we develop an optimized procedure to maximize stress resilience of yeast‐laden ELMs through the use of desiccant storage and 10% trehalose incubation before lyophilization. This approach led to over 1‐year room temperature storage stability across a range of strain genotypes. In particular, we highlight the superiority of exogenously added trehalose over endogenous, engineered production in yielding robust preservation resilience that is independent of cell state. This simple, effective protocol enables sufficient accumulation of intracellular trehalose over a short period of contact time across a range of strain backgrounds without requiring the overexpression of a trehalose importer. A variety of microscopic analysis including µ‐CT and confocal microscopy indicate that cells form spherical colonies within F127‐BUM ELMs that have variable viability upon storage. The robustness of the overall procedure developed here highlights the potential for widespread deployment to enable on‐demand, cold‐chain independent bioproduction.